2014
DOI: 10.1182/blood-2014-03-563056
|View full text |Cite
|
Sign up to set email alerts
|

Evolving use of new oral anticoagulants for treatment of venous thromboembolism

Abstract: The new oral anticoagulants (NOACs), which include dabigatran, rivaroxaban, apixaban, and edoxaban, are poised to replace warfarin for treatment of the majority of patients with venous thromboembolism (VTE). With a rapid onset of action and the capacity to be administered in fixed doses without routine coagulation monitoring, NOACs streamline VTE treatment. In phase 3 trials in patients with acute symptomatic VTE, NOACs have been shown to be noninferior to conventional anticoagulant therapy for prevention of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
98
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 45 publications
0
98
0
6
Order By: Relevance
“…The non-vitamin K antagonist oral anticoagulants (NOAC) have the potential to allow patients to be treated by monotherapy from acute to chronic phase, which is a long-awaited treatment option; and to replace conventional therapy for VTE. 5 Apixaban is an orally administered reversible inhibitor that binds to blood coagulation activated factor X (FXa). 5 AMPLIFY, a multi-regional, randomized, double-blind, active-controlled study in which Japanese subjects were not included, showed that a fixed-dose regimen of oral apixaban alone was as effective as conventional treatment consisting of enoxaparin followed by warfarin, and was associated with a clinically relevant reduction of 69% in major bleeding, indicating that apixaban can provide a simple, effective, and safe regimen for the initial and long-term treatment of VTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-vitamin K antagonist oral anticoagulants (NOAC) have the potential to allow patients to be treated by monotherapy from acute to chronic phase, which is a long-awaited treatment option; and to replace conventional therapy for VTE. 5 Apixaban is an orally administered reversible inhibitor that binds to blood coagulation activated factor X (FXa). 5 AMPLIFY, a multi-regional, randomized, double-blind, active-controlled study in which Japanese subjects were not included, showed that a fixed-dose regimen of oral apixaban alone was as effective as conventional treatment consisting of enoxaparin followed by warfarin, and was associated with a clinically relevant reduction of 69% in major bleeding, indicating that apixaban can provide a simple, effective, and safe regimen for the initial and long-term treatment of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…5 Apixaban is an orally administered reversible inhibitor that binds to blood coagulation activated factor X (FXa). 5 AMPLIFY, a multi-regional, randomized, double-blind, active-controlled study in which Japanese subjects were not included, showed that a fixed-dose regimen of oral apixaban alone was as effective as conventional treatment consisting of enoxaparin followed by warfarin, and was associated with a clinically relevant reduction of 69% in major bleeding, indicating that apixaban can provide a simple, effective, and safe regimen for the initial and long-term treatment of VTE. 6 Moreover, it would be of great interest to determine the health economics of NOAC for VTE, and several reports including from The National Institute for Health and Care Excellence indicated that apixaban could be considered a clinically and cost-effective option for VTE.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the RE-LY trial showed that compared with Warfarin the oral direct thrombin inhibitor, Dabigatran etexilate given at a dose of 150 mg twice daily reduces stroke with less intracranial bleeding, and Dabigatran 110 mg twice daily has similar efficacy with less bleeding [19]. The rate of major bleeding was 3.36% per year in the Warfarin group, as compared with 2.71% per year in the group that received 110 mg of Dabigatran (relative risk with Dabigatran, 0.80; 95% CI, 0.69 to 0.93; P = 0.003) and 3.11% per year in the group that received 150 mg of Dabigatran [19].Despite this better performance of dabigatran than warfarin in the bleeding scenario, there are still various emergent situations where the presence of Dabigatran in the blood system may worsen the hemorrhagic event [22][23][24]. Serious bleeding can occur.…”
mentioning
confidence: 96%
“…Despite this better performance of dabigatran than warfarin in the bleeding scenario, there are still various emergent situations where the presence of Dabigatran in the blood system may worsen the hemorrhagic event [22][23][24]. Serious bleeding can occur.…”
mentioning
confidence: 99%
“…With half-lives of about 12 hours, the ODIs also have a rapid offset of action [17]. All-oral regimens of revaroxaban and apixaban are available out-of-hospital treatment [17].…”
Section: New Oral Anticoagulants: the Direct Oral Inhibitorsmentioning
confidence: 99%